Wear behaviour of TiC coated AISI 4340 steel produced by TIG surface melting - Maleque, Md. Abdul; Ghazal, Belal Ahmed; Ali, Mohammad Yeakub; Hayyan, Maan; Ahmed, Abu Saleh (Trans Tech Publications, 2015)
Coating possesses superior wear resistance which makes the material suitable for components subjected to dynamic applications under sever wearing condition and high temperature applications. In this study, TiC coating layer was synthesized by preplacing a 1 mg/mm2 of fine size (~40 μm) TiC powder on the surface of AISI 4340 steel. The composite layer was produced by rapidly melting TiC powder together with the substrate steel using tungsten inert gas (TIG) torch welding at a fixed heat input of 1344 J/mm. The wear behaviour of the coated steel was investigated using a universal pin-on-disc tribometer. The microhardness profile of the coating showed increment of the hardness value (almost 5 times higher) than the substrate material. The wear test results showed that the TiC coated steel has lower wear volume loss hence, higher wear resistance compared to the substrate AISI 4340 steel. Incorporation of TiC into the steel surface has improved the wear behaviour of the steel by reduction of plastic deformation and ploughing of the steel surface. The SEM micrograph of the wear worn surface showed mild type of abrasive wear for coated steel whereas, the AISI 4340 steel showed severe type wear with excessive plastic deformation and ploughing.